China, Indonesia, dan ASEAN: Suatu Tinjauan - Sahrasad, Herdi (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2017)
China's history shows that China's acceptance of international norms comes not only from the national interest but also influenced by the political system and social values that have shaped its relationship with Southeast Asia over 2000 years. Today Southeast Asia is still based on the question of how to adapt to new developments in Asia that are uncertain about how to defend themselves against and manage their country to face global markets and national power that have imperial potential. There has been a considerable amount of history written these two centuries to remind the local leaders to cooperate with each other. It is time to consolidate Southeast Asian regional groupings that can protect the long-term interests of the region.